292P Erectile dysfunction among male lymphoma survivors in a developing country - Ng, Diana Leh-Ching; Gan, G. G.; Leong, Y. C. (Oxford University Press, 2018)
Background: Although erectile dysfunction (ED) is one of the known long-term complications among male cancer survivors, it is not commonly reported particularly in South East Asian region. This study aims to determine the prevalence of ED in lymphoma survivors in Malaysia and to determine its association with anxiety and depression, and its effects on patients’ quality of life (QOL).